Application of Vacuum Infiltration in Cryopreservation of Isolated Grape Buds - Prystalov, Anton; Bobrova, Olena; Kuleshova, Larisa (Problems of Cryobiology and Cryomedicine, 2021)
Preserving the gene pool of grapes, referred to the vegetatively propagated plants is a complicated task, which can be also solved by cryopreservation of the buds. To saturate such bulk and heterogeneous samples with cryoprotectants the novel methods are required. The effectiveness of vacuum infiltration and 60 min standard passive saturation (soaking) of isolated grape buds of the Russian Concord variety with a cryoprotective solution PVS 2 were compared in this research. To saturate by vacuum infiltration the buds were incubated in cryoprotective solution for 15 min at 40 kPa, afterwards, the pressure was gradually increased to atmospheric level. The efficiency of bud saturation was evaluated with low-temperature differential scanning calorimetry by changing the enthalpies and temperatures of phase transitions as well as the intensity of heat capacity jump at glass transition. The use of vacuum in the saturation of isolated grape buds were found to lead to a strong rise in cryoprotectant concentration in them and a significant decrease in the amount of free water crystallized during cooling compared to passive soaking in a PVS 2 vitrification solution. Probl Cryobiol Cryomed 2021; 31(1): 051–057